Instrumenty zarządzania kosztami w zarządzaniu przez wartość - Wierzbiński, Marcin (Cost Management Instruments in Value Based Management, 2005)
In the article the author tries to show the role of different cost management methods in value based management (VBM). In the beginning, the paper presents connection between cost management and creating value for shareholders. Then three cost management methods are analyzed in the context of value based management. The author analyzes the following methods: product life cycle costing, target costing, activity based costing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 299-305